Walk two moons - Creech, Sharon (HarperTrophy, 1996)
After her mother leaves home suddenly, 13-year-old Sal and her grandparents take a car trip retracing her mother's route. Along the way, Sal recounts the story of her friend Phoebe, whose mother also left.